« Notre âme est un tableau mouvant ». Énergétique des émotions et puissance de l’image chez Diderot - Jean-Louis Haquette (Acta Universitatis Carolinae: Philologica, 2018)
In the broader context of the sensualist theory of passions, Diderot ’s thought on drama and painting is an interesting point of view on the links between visuality and emotions in the 18th century. The image of the “tableau mouvant” is revealing of the opposition between images and language in the expression of emotions, and, in Diderot ’s view, the inferiority of the latter. In several moments of different texts concerning passions and emotions, the totum simul of images is opposed to the successive dimension of language. Accordingly, the poetics of drama relies heavily on gesture and pantomime, when a sublime movement is more meaningful than a long discourse. In the artistic communication of emotions, visual efficiency is the touchstone of success for Diderot, as in his analysis of the failed portrait of Mademoiselle Clairon by Van Loo. In a more unexpected way, the expressive body also plays an important role in Diderot ’s reaction to Richardson novels. It fosters an integration of detailed gestures in both Le Neveu de Rameau and La Religieuse, where Diderot skilfully plays with dramatic visual expressivity.